2014
DOI: 10.1016/j.envpol.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and removal pathways of four common PPCP/EDCs in soil

Abstract: Pharmaceutical and personal care products (PPCPs) and endocrine disrupting chemicals (EDCs) enter the soil environment via irrigation with treated wastewater, groundwater recharge, and land application of biosolids. The transformation and fate of PPCP/EDCs in soil affects their potential for plant uptake and groundwater pollution. This study examined four PPCP/EDCs (bisphenol A, diclofenac, naproxen, and 4-nonylphenol) in soil by using 14C-labeling and analyzing mineralization, extractable residue, bound resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…14 C-naproxen and 14 C-diclofenac were found to be mainly (up to 50-80%) mineralized to 14 CO 2 in different soils (Dodgen et al, 2014;Topp et al, 2008), while only a small part of 14 C-carbamazepine (b1.2%) and 14 C-acetaminophen (17%) were mineralized . Some metabolites of pharmaceuticals in soils were identified by using a combination of techniques, including 14 C labeling, LC fractionation, and LC-MS/MS structural elucidation (Dodgen et al, 2014;Li et al, 2013Li et al, , 2014. It was reported that acetaminophen was rapidly converted to various metabolites in soils , while slow and limited transformation was observed for carbamazepine .…”
Section: Fate Of Ppcps In Soilmentioning
confidence: 98%
“…14 C-naproxen and 14 C-diclofenac were found to be mainly (up to 50-80%) mineralized to 14 CO 2 in different soils (Dodgen et al, 2014;Topp et al, 2008), while only a small part of 14 C-carbamazepine (b1.2%) and 14 C-acetaminophen (17%) were mineralized . Some metabolites of pharmaceuticals in soils were identified by using a combination of techniques, including 14 C labeling, LC fractionation, and LC-MS/MS structural elucidation (Dodgen et al, 2014;Li et al, 2013Li et al, , 2014. It was reported that acetaminophen was rapidly converted to various metabolites in soils , while slow and limited transformation was observed for carbamazepine .…”
Section: Fate Of Ppcps In Soilmentioning
confidence: 98%
“…There is evidence that PhACs can be attenuated during transport by soil materials into groundwater from surface water (Bradley et al, 2014). Degradation occurring in the soil environment has been observed to result in PhAC transformation products due to chemical transformations of the parent compound (Dodgen et al, 2014;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Studies with soil/sediment systems have found 4′-hydroxy-DCF (4HD), 5-hydroxy-DCF (5HD) and a 5HD derivative, 5HD-quinone imine (5HDQI) (Gröning et al., 2007). Another study dealing with the fate of DCF in soil identified the formation of 5HD and several isomers of dichlorobenzoic acid (Dodgen et al., 2014). The principal human metabolites of DCF are 4HD and 5HD (Stierlin et al., 1979).…”
Section: Introductionmentioning
confidence: 99%